PENGARUH GAYA HIDUP SEHAT DAN CITRA MEREK TERHADAP PREFERENSI KONSUMEN MINUMAN RTD (READY TO DRINK) DI KALANGAN MAHASISWA KAMPUS U NESA KETINTANG (CASE: COCA=COLA ZERO SUGAR & TEH BOTOL SOSRO TAWAR) - Fahreza Megananda; Sanaji Sanaji (Jurnal Ilmu Manajemen, 2021)
This study examines and analyses the influence of a healthy lifestyle and brand image on consumer preferences for ready-to-drink. The population for this research is ready-to-drink (RTD) consumers, students from the State University of Surabaya on the Ketintang campus. The categories of ready-to-drink that became the research object were Coca-Cola Zero Sugar and The Botol Sosro Tawar. This study uses a quantitative approach with a sampling technique using a non-probability sampling method. The number of samples used by researchers in this study was 116 samples according to Machin and Champbell (1987). The statistic used is multiple linear regression with the help of IBM SPSS Statistics 25.0. The results show that a healthy lifestyle and brand image positively and significantly affect consumer preferences. Based on these results, "RTD" beverage manufacturers must pay attention to changes in consumer lifestyles that are healthier so that they can bring up innovations to meet consumer needs. In addition, it must also improve its brand image so that it can always be an option for consumers of "RTD" drinks.